2020
DOI: 10.1016/j.scitotenv.2020.140598
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide lifecycle management in agriculture and public health: Where are the gaps?

Abstract: Pesticide lifecycle management encompasses a range of elements from legislation, regulation, manufacturing, application, risk reduction, monitoring, and enforcement to disposal of pesticide waste. A survey was conducted in 2017–2018 to describe the contemporary global status of pesticide lifecycle management, to identify where the gaps are found. A three-tiered questionnaire was distributed to government entities in 194 countries. The response rate was 29%, 27% and 48% to the first, second and third part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 19 publications
0
28
0
4
Order By: Relevance
“…It is a fact that no developing country will ever possess the resources needed to maintain comprehensive control over all the components of pesticides lifecycles. In a study conducted by Van den Berg et al. (2020) on gaps in the pesticide lifecycle management in agriculture and public health in both developed and developing countries, it was shown that global shortcomings exist but are more aggravated in the developing countries ( Van den Berg et al., 2020 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a fact that no developing country will ever possess the resources needed to maintain comprehensive control over all the components of pesticides lifecycles. In a study conducted by Van den Berg et al. (2020) on gaps in the pesticide lifecycle management in agriculture and public health in both developed and developing countries, it was shown that global shortcomings exist but are more aggravated in the developing countries ( Van den Berg et al., 2020 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In a study conducted by Van den Berg et al. (2020) on gaps in the pesticide lifecycle management in agriculture and public health in both developed and developing countries, it was shown that global shortcomings exist but are more aggravated in the developing countries ( Van den Berg et al., 2020 ). It is also a fact that no country in the world, even the wealthiest one, will ever have the ultimate lifecycle management performing at 100% certainty ( Centner, 2018 ; Stehle and Schulz, 2015 ; Storck et al., 2017 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions with binary or numeric responses were selected for analysis. Questions with narrative responses, questions that appeared to be ambiguous in retrospect, and several questions that had been used in a more broad-based pesticide study [12] were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of results, countries were grouped according to the United Nations Regional Groups of Member States[13]. This classi cation differentiates the African, Asia-Paci c, Latin American & Caribbean, were pooled together with those of the Western European & Others Group into the 'European & Others Group'.…”
mentioning
confidence: 99%